KERJASAMA TEKNIK MILITER INDONESIA DAN RUSIA DALAM PEMBELIAN PESAWAT SUKHOI Su-30MK2 TAHUN 2006-2010 - Widi Agra Agatha; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research explains about Militery Technique cooporation between Indonesia and Russia in term of the trade agreement of Sukhoi Su-30MK2 in 2006-2010. The agreement if Security Cooperation is written in Memorandum of Understanding (MoU) which was agreed on 21 in April 2003.The data of this research were acquired from journals, offical documents, minithesis, books, and internet to analyze cooperation of military technique in term of the trade agreement of Sukhoi Su-30MK2 aircraft between Indonesia and Russia. This research use’a Realist point of view and International Cooperations Theory.This research proves that the history between the two countries takes the main role in this cooperation. On the other hand the Military technique cooperation between Indonesia and Rusia has an effect in air military measures power which includes purchasing Sukhoi Su-30MK2. This trade will increase the capabilities of indonesia’s national security. The prime benefit that indonesia will achieve the increasing of the air measure capability.Keyword: Military Techinque cooporation, Indonesia and Russia, trade agreement of Sukhoi Su-30MK2